Mal-estar na adolescência: jovens de agendas lotadas nas redes sociais - Matta, João Osvaldo Schiavon (2012)
In this thesis we researched on the consumption of young people on internet social networks. Beyond the simple act of buying products, we mean consumption as a code which reflects the relationship of young people, linking them to three dimensions: consumption of technology, information and symbolic capital, which is represented here by the media visibility. More specifically, we answer the following questions: are the adolescents really digital natives with high experience and extensive technical competence using social network on the internet, such as widespread the common sense? How is the everyday practice of consumption of young people? In order to answer this, throughout eight months, we use tools like Skype, e-mail, and Facebook to communicate with the young participants of this study, whose day-to-day we have participated. The group was made up of students from three high schools of Sao Paulo´s countryside, two of them being private school and other one public, their age ranged between twelve and seventeen years old, who are owners of their own technical devices to access the web. The theoretical framework from this research includes the Anthropology of Consumption, and Material Culture studies, which are able to reveal how new technologies are being assimilated into their different users. Few important names of these fields of knowledge are Daniel Miller, Dan Slater, Roberta Sassatelli, and Grant McCraken. Methodologically, the research drove different strategies, such as interviews, monitoring of participants, and building a field diary. Considering the three dimensions of this research consumption of technology, information, and symbolic capital we have seen intense consumption practices, related to a routine of hectic schedules, which is a source of intense stress, and discontents for adolescents, as seen in adulthood